The disposition effect in team investment decisions: Experimental evidence - Rau, Holger A. (Journal of Banking & Finance, 2015)
This paper experimentally studies the disposition effects of teams and individuals. The disposition effect describes the phenomenon that investors are reluctant to realize losses, whereas winners are sold too early. Our experiments compare the investments of two-person teams to a setting where investors trade alone. We find that subjects investing jointly exhibit more pronounced disposition effects than individuals. A closer look reveals that investor teams hardly realize losses and predominately sell winners. The data suggest that decision-dependent emotions may explain the differences. That is, teams reporting high levels of regret exhibit significantly higher disposition effects than individuals.